Understanding the effects of soil data quality on SWAT model performance and hydrological processes in Tamedroust watershed (Morocco). (December 2019) - Bouslihim, Yassine; Rochdi, Aicha; El Amrani Paaza, Namira; Liuzzo, Lorena
Abstract: Hydrological modeling remains an indispensable tool for water resources research in order to understand the watershed functioning and to effectively manage water supplies. The study of the hydrologic functioning of a semi-arid watershed is a real challenge in the lack of reliable and regular data. In this work, we propose (1) to evaluate the performance of Soil and Water Assessment Tool (SWAT) on the TAMEDROUST watershed (Morocco) under extremely contrasted climatic conditions during the period 1998–2002 and (2) to test the effects of the soil data resolution on the watershed response. For this second purpose, two soil databases are compared: (i) HWSD-2L, a low-resolution soil database with three soil types obtained from the Harmonized World Soil Database produced by FAO and (ii) TAMED-SOL, a refined database with eleven soil types, performed from field measurements and laboratory analyses. Results before calibration showed a considerable variability and a significant effect of the soil characteristics on the different components of the hydrological cycle such as SW (soil water content) and GWQ groundwater discharge into reach). Flows obtained by HWSD-2L soil database were consistently lower than those simulated by TAMED-SOIL but both databases overpredicted streamflow if compared to observed data. To harmonize the data of the two databases, we proceeded to a harmonization of the soil depth by considering in HWSD-2L only the surface layer, thus creating a third database HWSD-1L which was also considered in the evaluation of the model response. After the calibration period, both soils databases (TAMED-SOIL and HWSD-2L) improved the model performance in terms of streamflow, with values of R 2 and NSE between 0.64 and 0.65. Model validation was acceptable and similar for both databases with R 2 and NSE values of 0.76 and 0.57. We can conclude that the quality and resolution of soil data affects all hydrological cycle components, mainly SW and water yield (WYLD), but do not lead to significant discrepancies in streamflow simulation, especially after the model calibration. Highlights: Creation of a personal refined soil database in Tamedroust watershed (TAMED-SOIL). Adaptation of a global Harmonized World Soil Database (HWSD) produced by FAO to the studied watershed. Effects of quality and resolution of soil database on the hydrological cycle components. Soil water content (SW) is the most sensitive component of soil data quality. Calibration and Validation results are statistically satisfactory.